Aplikasi ArcGIS Untuk Analisa Laju Erosi Dan Upaya Konservasi Lahan DAS Wlingi Provinsi Jawa Timur - Pujanarko, Oktavian Anggih; Sisinggih, Dian; Asmaranto, Runi (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
Wlingi Watershed at river flow Brantas River and located in the Jegu Village and is about 16 km east of Blitar City. The inhabitants of Wlingi Basin are predominantly farmers and thus have great potential to increase the acceleration of land conversion in the watershed. Estimation of erosion and integrated conservation techniques is needed in managing the Wlingi Basin, so its utilization can be run optimally and maintained to be utilized by future generations. This study aims to find out distribution of level of erosion grade in 2011, 2016 and after simulation of land conservation changes in Wlingi Basin. The method used is USLE (Universal Soil Loss Equation) with ArcGIS software. From the result of analysis it was found that level of erosion grade of 2016 in the Wlingi Basin area covered by very slight (<1,75 tons/ha/year) to very severe (>92,5 tons/ha/year) with percentage of erosion grade 35,23%, 31,70%, 18,11%, 6,71% dan 8,24% respectively. Land conservation directives are carried out to reduce the rate of erosion. The post-conservation in the Wlingi Basin area includes very  slight  to  very  severe  with  the  percentage of  47,68%,  31,43%,  9,66%,  6,10%  dan  5,12%. Decreased erosion rates are good occured following the simulation of land conservation, so land conservation is a mandatory for sustainable land using.